Efficient preparative synthesis of isoflavones with the amide function - Moskvina, V. S.; Shablykina, O. V.; Ishchenko, V. V.; Khilya, V. P. (Reports of the National Academy of Sciences of Ukraine, 2015)
The reactivity of amides of 2-hydroxydezoxybenzoine-2′-carboxylic acids is investigated. A convenient method to obtain isoflavones with a carboxamide group is developed, using the interaction 2-[2-(morpholin-4-ylcarbonyl)phenyl]-1-(2-hydroxyphenyl)ethanones with DMFDMA. Acetylation of 2-[2-(morpholin-4-ylcarbonyl)phenyl]-1-(2-hydroxyphenyl)ethanones in basic solutions passes to the cyclization to form an isocoumarin system.